The Rise, Fall, and Resurgence of Home Hemodialysis. Issue 2 (8th January 2017) - Trinh, Emilie; Chan, Christopher T.
Abstract: Home hemodialysis (HD) was first introduced in the 1960s with a rapid increase in its use due to inability of dialysis units to accommodate patient demand. A sharp decline was subsequently seen with expanding outpatient dialysis facilities and changes in reimbursement policies. In the last decade, with emerging reports of benefits with home HD and more user‐friendly equipment, there has been resurgence in home HD. However, home HD remains underutilized with considerable variations between and within countries. This paper will review the history of home HD, elaborate on its established benefits, identify some of the barriers in uptake of this modality and expand on potential strategies to overcome these barriers.